Ferroptosis plays a novel role in nonalcoholic steatohepatitis pathogenesis - Fei Xiong; Qiao Zhou; Xiaobo Huang; Peng Cao; Yi Wang (Frontiers Media S.A., 2022)
Ferroptosis relies on iron, and ferroptotic cell death is triggered when the balance of the oxidation-reduction system is disrupted by excessive lipid peroxide accumulation. A close relationship between ferroptosis and nonalcoholic steatohepatitis (NASH) is formed by phospholipid peroxidation substrates, bioactive iron, and reactive oxygen species (ROS) neutralization systems. Recent studies into ferroptosis during NASH development might reveal NASH pathogenesis and drug targets. Our review summarizes NASH pathogenesis from the perspective of ferroptosis mechanisms. Further, we discuss the relationship between mitochondrial dysfunction, ferroptosis, and NASH. Finally, potential pharmacological therapies directed to ferroptosis in NASH are hypothesized.